How to be a good teacher - Nazarqosimova, Ozoda Sobir qizi; Axmedov, Sobir Nazarqosimovich (Science and Education, 2023)
This paper discusses the qualities of good teachers in relation classroom teaching. The paper highlighted how to become a good teacher. It also offers suggestions how good teachers can be produced .It concludes that a good teacher or one, who want to be, should have all the general attributes and qualities of a good professional classroom teacher so that they can excel and have good and effective performance in the classroom.